Climate-smart lunches: Conclusions on food waste and associated GHG emissions at the 5th Global CSA Conference - Broeze, Jan (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Presentation by Jan Broeze, WUR-CCAFS food loss and waste (FLW) project leader, at the 5th Global Conference on Climate-Smart Agriculture in Bali on 10 October 2019.